2003
DOI: 10.1152/ajpregu.00732.2002
|View full text |Cite
|
Sign up to set email alerts
|

Gastric distension induces c-Fos in medullary GLP-1/2-containing neurons

Abstract: A group of neurons in the caudal nucleus of the solitary tract (NTS) processes preproglucagon to glucagon-like peptides (GLP)-1 and -2, peptides that inhibit food intake when administered intracerebroventricularly. The GLP-1/2-containing neural pathways have been suggested to play a role in taste aversion and nausea because LiCl activates these neurons, and LiCl-induced suppression of food intake can be blocked by the GLP-1 receptor antagonist exendin-9. As many gastrointestinal signals related to both satiety… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
152
1
5

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 188 publications
(164 citation statements)
references
References 46 publications
6
152
1
5
Order By: Relevance
“…Furthermore, in rats GLP-1-producing neurons are activated by distension of the stomach and enteroceptive stress [27,28]. This could indicate a neuronal transmission of satiety signals from the gastrointestinal tract into the brain through the "brain GLP-1 system".…”
Section: Glucagon-like Peptide-1 (Glp-1) Physiologymentioning
confidence: 99%
“…Furthermore, in rats GLP-1-producing neurons are activated by distension of the stomach and enteroceptive stress [27,28]. This could indicate a neuronal transmission of satiety signals from the gastrointestinal tract into the brain through the "brain GLP-1 system".…”
Section: Glucagon-like Peptide-1 (Glp-1) Physiologymentioning
confidence: 99%
“…We were struck by this expression pattern, as medial NTS neurons were also known to process GI vagal afferent signals arising from ingesta interacting with the stomach and intestine, [54][55][56][57][58][59] and set out to address whether leptin signaling (intraperitoneal leptin-induced pSTAT3-IR) and physiological levels of gastric distension-induced Fos-IR were expressed by the same NTS neurons. We found that B40% of pSTAT3-IR medial NTS neurons are also responsive to gastric distention.…”
Section: Glp-1mentioning
confidence: 99%
“…The NTS receives a broad spectrum of sensory signals from the gut, carried in part by the subdiaphragmatic vagus nerve; signals include sensory input from liver, stomach, and intestinal receptors (Powley, 2000;Saper et al, 2002;Vrang et al, 2003). These signals may be associated with the homeostatic control of feeding, and possibly involved in initiation or termination of meals (Saper et al, 2002).…”
Section: Functional Considerationsmentioning
confidence: 99%